A instrumentalização musical para sensibilização ambiental e ações referentes aos impactos socioambientais no rio do Peixe, em Coronel João Sá/BA - Silva, Luciano Andrade da (2019)
The environmental problem becomes evident from the 60's, considering the limits of nature in relation to economic rationality, increasing urbanization and the fractionation of knowledge. Thus, the school plays an important role in sensitizing students and the community to the social and environmental impacts, since it plays a significant social role in the critical citizen formation, participative and conscious in the face of environmental problems. Therefore, the research aimed to sensitize the ecological subjects of the State School Santo Antônio State through musical instrumentalization about the social and environmental impacts of the Peixe River, in Coronel João Sá city (Bahia). For this, it started from the socio-environmental problem in the Peixe River that affects the population in obtaining life quality. Thus, the hypothesis that guided the research was that through musical instrumentalization in the school context it is possible to provide recognition of local reality, sensitizing students in search of actions to minimize local socio-environmental impacts. Thereby, the action-research provided support for this study, as it is conceived and performed by the search for the resolution of a collective problem. Regarding the methodological procedures were carried out bibliographic and documentary studies, questionnaire application, brainstorming, workshops for making instruments with recyclable materials, pedagogical action associated with the study of the environment, photographic record and use of drone. The field activity made it possible to bring the school closer to its surroundings, allowing students to observe and analyze local socio-environmental problems. Therefore, the results obtained throughout the process were expressed through didactic productions (documentary video, mockups, puppet theater, painting and creation of music lyrics), unfolded in the construction of the manifest letter delivered to the City Council. Continuing the research and the actions developed, the musical instrumentalization was accomplished through the creation of a percussion with recyclable materials, which generated several products, such as a video clip with the songs of the studants. Thus, the research enabled the development of educational practices beyond information, since the construction of knowledge was not restricted in the school environment, proving to be effective in activities that allowed ecological subjects to associate the systematized knowledge with the local reality of the social and environmental impacts of the Peixe River through musical art for environmental awareness not only at school, but in the community itself.